Konseling Pranikah Dan Pemberian Informasi Psikologi Perkawinan Untuk Membentuk Keluarga Sakinah Pada Calon Pengantin Di Kantor Urusan Agama Kecamatan Lubuk Kilangan - Rahmadianti Aulia; Hasneli (Universitas Negeri Padang, 2022)
The family is the smallest social unit that has a very large role and contribution in creating a quality generation. Prospective bright generations will be born from sakinah, mawaddah and rahmah families. However, with the high divorce rate, it is proof that the quality of the family is still far from expectations. In addition, considering the high number of marriages, reaching 40 pairs per month who are married at KUA, Lubuk Kilangan District, the purpose of this service is to provide marriage psychology information and pre-wedding courses to prospective brides so as to be able to increase knowledge and understanding of prospective brides, especially those who will marry at KUA. Lubuk Kilangan District. Marriage psychology material is given through lectures, then a pocket book is given to each bride and groom that contains information related to marital psychology which includes family psychology. In addition, pre-marital counseling was carried out and a WhatsApp group was formed to accommodate questions and problems of the prospective bride and groom. This activity is effective in increasing the knowledge and knowledge of the prospective bride and groom in marital psychology material as their provision in dealing with problems in their household in the future. The enthusiasm and activeness of the participants during the activities and in the discussions that have been held can be seen. In addition, participants were also active in expressing their knowledge and curiosity through the counseling groups that had been held. Finally, the KUA also hopes that similar activities will be carried out to assist the KUA in providing knowledge to the bride and groom, especially in the field of psychology.